Eustachian Tube Teratoma: A Rare Entity - Dan Cristian Gheorghe; Augustina Enculescu; Adina Elena Stanciu; Veronica Epure; Adina Zamfir- (SAGE Publishing, 2023)
Introduction: Teratomas, tumors derived from all 3 fetal germ cell layers, are rarely located in the head and neck region and extremely rare in the Eustachian tube area. Case report: The authors present the case of a 2 years old child with chronic ear discharge. Referral diagnosis was tumor or cyst of the temporal bone. Intraoperatively, a solid, hairy tumor located inside the Eustachain tube, with extension into the middle ear space was discovered and removed. Histology revealed a mature teratoma. Review of the literature showed reports of rare similar cases of Eustachian tube teratomas, differentiating themfrom hairy polyps of the rhynopharynx. The imaging of our patient, the surgical techique for removal of the tumor and long term follow-up are detailed. Conclusions: Teratomas located inside the Eustachian tube are exceptional. Their removal should be carefully planned in view of their long term anatomical sequelae and in order to avoid long term postoperative morbidity.